66+6(x-1)=90

Simple and best practice solution for 66+6(x-1)=90 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 66+6(x-1)=90 equation:


Simplifying
66 + 6(x + -1) = 90

Reorder the terms:
66 + 6(-1 + x) = 90
66 + (-1 * 6 + x * 6) = 90
66 + (-6 + 6x) = 90

Combine like terms: 66 + -6 = 60
60 + 6x = 90

Solving
60 + 6x = 90

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-60' to each side of the equation.
60 + -60 + 6x = 90 + -60

Combine like terms: 60 + -60 = 0
0 + 6x = 90 + -60
6x = 90 + -60

Combine like terms: 90 + -60 = 30
6x = 30

Divide each side by '6'.
x = 5

Simplifying
x = 5

See similar equations:

| (3r)r=8r | | 0.2p+0.9=3.5-0.5p | | 2.5x=6-1.5x | | 3-10=z/(-8) | | 66+6(x+1)=180 | | Tan(x)=0.593 | | 100-20-x=25 | | (3r)(3r)=8r | | 20/x-2=5 | | 20n=160 | | M-3/10=5/8 | | 0.5(2-a)=0.2(2a-6) | | 9x+3(800-x)=30 | | x/5=0.5 | | (5x-7)(7x+4)=0 | | -4(v+6)=4 | | 11n=115 | | -3.2y+1.4=-0.8(9y-5) | | 3(2x-5)+15=7x-6 | | .28x-.75x=-13 | | 5/36-3/4 | | 62-3x=9-8x | | 0.2b+0.7=-3.7-0.8b | | -4(2-4x)+3= | | 4n=148 | | -x^2+8x+48=0 | | 0.35(80)+0.15z=0.25(80+z) | | x-2:/:3=1 | | sin(10x)=0.5 | | 0.30c+60.90=c | | 20.8b+2.1=10.5b+22.7 | | 10/9-2/3 |

Equations solver categories